2018
DOI: 10.1183/13993003.02211-2017
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal replacement

Abstract: Tracheal reconstruction is one of the greatest challenges in thoracic surgery when direct end-to-end anastomosis is impossible or after this procedure has failed. The main indications for tracheal reconstruction include malignant tumours (squamous cell carcinoma, adenoid cystic carcinoma), tracheoesophageal fistula, trauma, unsuccessful surgical results for benign diseases and congenital stenosis. Tracheal substitutes can be classified into five types: 1) synthetic prosthesis; 2) allografts; 3) tracheal transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
129
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(132 citation statements)
references
References 47 publications
(66 reference statements)
0
129
0
3
Order By: Relevance
“…Butler et al () also reported that the vacuum‐assisted decellularization of tracheal graft results better graft for clinical application. Clinical study of acellular graft was done for the tracheal tissue reconstruction (Elliott et al, ; Etienne et al, ; Li et al, ; Martinod et al, ).…”
Section: Progress In Tracheal Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Butler et al () also reported that the vacuum‐assisted decellularization of tracheal graft results better graft for clinical application. Clinical study of acellular graft was done for the tracheal tissue reconstruction (Elliott et al, ; Etienne et al, ; Li et al, ; Martinod et al, ).…”
Section: Progress In Tracheal Tissue Engineeringmentioning
confidence: 99%
“…The common therapy used for the treatment of damaged tracheal tissue is “direct anastomosis,” “suboptimal laser treatment,” and “stenting.” There are many other treatments, such as autografting and allografting: Use of prosthetic materials or a combination (e.g., silk‐coated titanium mesh) has also been attempted (Graziano, Spinazzola, & Neville, ; Okumura, Nakamura, Shimizu, Natsume, & Ikada, ). Available prosthetics often have some limitations, such as incomplete host tissue integration and inflammation; they do not mimic native tissue properties and shows extrusion (Etienne et al, ; Kojima & Vacanti, ). However, in case of grafting, surgical outcomes are excellent without any rejection or inflammation when autograft is used.…”
Section: Introductionmentioning
confidence: 99%
“…Tracheal stenosis is usually caused by trauma, malignant neoplasms with airway involvement, and inherent factors (1). Most patients with long‐segment tracheal stenosis are often confronted with a poor prognosis because of a limitation in the materials available for tracheal reconstruction (2, 3).…”
mentioning
confidence: 99%
“…Tracheal resection can become necessary for malign or benign stenosis or fistulas (Etienne et al, 2018). When more than half of the length of the trachea (up to 5 cm) of adults or more than a third in children have to be resected, end-to-end-anastomosis is not possible due to increased strain on the tissue (Kucera, Doss, Dunn, Clemson, & Zwischenberger, 2007).…”
mentioning
confidence: 99%
“…When more than half of the length of the trachea (up to 5 cm) of adults or more than a third in children have to be resected, end-to-end-anastomosis is not possible due to increased strain on the tissue (Kucera, Doss, Dunn, Clemson, & Zwischenberger, 2007). As airway transplantation still has major shortcomings such as restenosis, immunological rejection, lack of blood supply, or infections, longer defects can only be treated palliatively (Delaere, 2012;Etienne et al, 2018) Thus, the development of an adequate tissue-engineered tracheal substitute is of high clinical interest. Three major shortcomings are described for current tissue engineered airway substitutes: a lack of mechanical stability, a missing long-term stable sealed connection to the patient's trachea, and an insufficient blood supply with nutrition of the engineered tissue in vivo (Law et al, 2016).…”
mentioning
confidence: 99%